Agroforestry orchards support greater avian biodiversity than monoculture oil palm and rubber tree plantations - Yahya, Muhammad Syafiq; Sharifah Nur Atikah; Mukri, Izereen; Sanusi, Ruzana; Norhisham, Ahmad Razi; Azhar, Badrul (Elsevier, 2022)
The suitability of agricultural matrices to support biodiversity, including birds, varies depending on agricultural land-use. In Southeast Asia, monoculture plantations of oil palm and rubber tree have replaced the native rainforests and displaced forest biodiversity. Compared to such single functionality plantations, agroforestry orchards may provide a more complex habitat for biodiversity via polyculture and less intensive farming practices. However, little is known about the conservation value of agroforestry orchards for biodiversity. Here, we investigated the effects of different agricultural habitats on avian biodiversity in Peninsular Malaysia. Using point count method, we assessed bird community in three focal agricultural habitats (i.e., agroforestry orchards, oil palm, and rubber tree plantations). From 6,248 bird encounters, we recorded 110 species comprising 43 families. Bird species richness and abundance were significantly greater in agroforestry orchards than the other two agricultural habitats. Bird abundance was similar in oil palm and rubber tree plantations, but the latter supported significantly more species. Agricultural land-use type had significant effects on certain bird dietary groups (i.e., frugivores, insectivores, omnivores, and granivores). Overlap in bird species composition between habitats was rather evident, though some bird groups were more represented than others in the different habitat types. Our key findings may imply the importance of habitat heterogeneity in relation to vegetation structural complexity (as commonly found in fruit orchards) on farmland birds. Our data suggest that incorporating diverse native fruit trees into large-scale monoculture plantations could promote habitat heterogeneity and floristic composition, which can improve bird conservation and ecosystem services (e.g., pest insect control).